Enhancement of the creation yield of NV ensembles in a chemically vapour deposited diamond. (July 2022) - Balasubramanian, Priyadharshini; Osterkamp, Christian; Brinza, Ovidiu; Rollo, Maxime; Robert-Philip, Isabelle; Goldner, Philippe; Jacques, Vincent; Jelezko, Fedor; Achard, Jocelyn; Tallaire, Alexandre
Abstract: In this work we investigate the properties of negatively charged nitrogen-vacancy (NV − ) centres created during single crystal diamond growth by chemical vapour deposition (CVD) on [113]-oriented substrates and with N2 O as a dopant gas. The use of spin echo and double electron-electron resonance (DEER) allows us to assess NV − ratio with respect to substitutional nitrogen impurities ( N s 0 ) incorporated during growth, a critical figure of merit for quantum technologies. We demonstrate that, at moderate growth temperatures (800 °C), dense NV − ensembles of several hundreds of ppb (800 ppb for 50 ppm of added N2 O) and with exceptionally high NV − / N s 0 ratios of up to 25% can be achieved. This NV − creation yield is higher by at least an order of magnitude to that typically obtained on standard [100]-grown diamonds and comparable to the best values reported for electron-irradiated diamonds. The material obtained here thus advantageously combines a high NV − density, high creation yield, long coherence times of several tens of μs together with a partial preferential orientation. These are highly desirable requirements for diamond-based quantum sensors that may spur new developments with this crystalline orientation leading to improved performance and sensitivity. Graphical abstract: Image 1 Highlights : Dense NV ensembles up to 800 ppb obtained on [113]-oriented diamond with N2 O as a dopant. Low temperature growth promotes nitrogen incorporation in the NV form. NV − / N s 0 creation yield measured by double electron-electron resonance. Highest NV − / N s 0 yield ever obtained in as-grown diamond of 25%.